Proceedings of the Symposium on Eye Tracking Research and Applications 2014
DOI: 10.1145/2578153.2578179
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of internal motor cues and external semantic cues to anticipatory smooth pursuit

Abstract: Smooth pursuit eye movements anticipate the future motion of targets when future motion is either signaled by visual cues or inferred from past history. To study the effect of anticipation derived from movement planning, the eye pursued a cursor whose horizontal motion was controlled by the hand via a mouse. The direction of a critical turn was specified by a cue or was freely chosen. Information from planning to move the hand (which itself showed anticipatory effects) elicited anticipatory smooth eye movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…3A), and reduced delay at reversal. This largely confirmed the findings of earlier studies showing more accurate ocular tracking of self-generated motion relative to tracking of external motion (Mather and Lackner 1980;Ross and Santos 2014) or tracking of passive movements (Steinbach 1969;Steinbach and Held 1968;Vercher et al 1995Vercher et al , 1996. As a novel manipulation in our paradigm, we varied the predictability of the dot motion in the control conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…3A), and reduced delay at reversal. This largely confirmed the findings of earlier studies showing more accurate ocular tracking of self-generated motion relative to tracking of external motion (Mather and Lackner 1980;Ross and Santos 2014) or tracking of passive movements (Steinbach 1969;Steinbach and Held 1968;Vercher et al 1995Vercher et al , 1996. As a novel manipulation in our paradigm, we varied the predictability of the dot motion in the control conditions.…”
Section: Discussionsupporting
confidence: 87%
“…However, in the current experiment we found that the LRP is strongly predictive of the start of the smooth pursuit eye movements. This explains why the smooth pursuit of self-motion has less lag and fewer saccades compared with the pursuit of external motion, as we observed in experiment 1 and previous studies (Gauthier and Hofferer 1976;Mather and Lackner 1980;Ross and Santos 2014;Scarchilli and Vercher 1999;Steinbach 1969;Steinbach and Held 1968;Vercher et al 1995).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One type of cue to the direction of future motion, which we may encounter frequently in natural situations, is the internal signal derived from our own motor commands whenever we control the motion of a target by ourselves. This situation was recently studied by Ross and Santos (2014).…”
Section: Anticipatory Responses With Self-generated Target Motionmentioning
confidence: 96%
“…An example is shown in Figure 8, which shows intersaccadic eye velocities were slow during a task that required guiding a mouse cursor through a displayed maze [Zhao & Marquez, 2013].) Ross and Santos (2014) studied the role of the motor signals used to control a target that was moved along the same cued or uncued paths illustrated in Figure 2. In their experiment a mouse was used to control the horizontal trajectory of motion of the target (the vertical motion was controlled by the software).…”
Section: Anticipatory Responses With Self-generated Target Motionmentioning
confidence: 99%